2003
DOI: 10.1258/002221503321626438
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of an empiric proton pump inhibitor trial vs 24-hour double-probe Ph monitoring in laryngopharyngeal reflux

Abstract: Laryngopharyngeal reflux (LPR), which is defined as the backflow of gastric contents into the upper aerodigestive tract, is a relatively common disorder. However, its diagnosis still poses many problems. Twenty-four-hour double-probe pH monitoring is currently the diagnostic test of choice, but it has many disadvantages. Thus, an empiric trial of antireflux therapy has been suggested as an alternative method for diagnosis. The purpose of this article is to evaluate the validity of this alternative method in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 16 publications
5
58
0
1
Order By: Relevance
“…3,13 Symptomatic improvement in patients in our study was seen after 2 months of therapy however improvement in laryngeal signs took 4 months. These results are similar to studies by Belafsky et al and Bilgen et al 3,14 Overall RFS showed significant change at 4 weeks of therapy and again at 8 and 24 weeks of therapy and this is similar to various other studies. 2,3 There is currently no accepted protocol for the most effective treatment for LPR.…”
Section: Discussionsupporting
confidence: 92%
“…3,13 Symptomatic improvement in patients in our study was seen after 2 months of therapy however improvement in laryngeal signs took 4 months. These results are similar to studies by Belafsky et al and Bilgen et al 3,14 Overall RFS showed significant change at 4 weeks of therapy and again at 8 and 24 weeks of therapy and this is similar to various other studies. 2,3 There is currently no accepted protocol for the most effective treatment for LPR.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, otolaryngologists should inquire regarding specific symptoms of LPR and also acknowledge nonspecific findings of laryngeal irritation and inflammation observed through laryngoscopic examination (17,18). RSI and RFS, developed by Belafsky et al (11,12), have been widely used for the diagnosis of LPR as they are simple, inexpensive, and noninvasive (14,19).…”
Section: Discussionmentioning
confidence: 99%
“…Limited data exist about the value of proximal pH probe monitoring in patients with chronic cough and GERD; however, many studies have shown the inefficiency of this technique for the diagnosis of laryngopharyngeal reflux . 33 MII-pH monitoring for the diagnosis of GERD allowed for the detection of gaseous and weak-nonacidic reflux in addition to acidic and liquid reflux. Proximal reflux episodes and nonacidic reflux associated with cough episodes have been observed in a small portion of the patient population, and an increase in reflux episodes in patients with chronic cough compared to healthy volunteers is seldom observed.…”
Section: Discussionmentioning
confidence: 99%